Intergenerational Transfers of Infant Mortality in 19th-Century Northern Sweden - Göran Broström; Sören Edvinsson; Elisabeth Engberg (Historical Life Course Studies)
This contribution is part of an international comparative initiative with the aim to assess the analytical power of the Intermediate Data Structure (IDS) in a study of possible intergenerational transmissions of death in infancy. An evaluation of the data in applied research will be useful for further development of the IDS structure and for its future use in comparative research. An additional methodological aim for this part of the study is to evaluate and compare different models for statistical analysis of intergenerational transfers. The analysis is based on a cohort of mothers born 1826-1854, whose experiences of infant mortality are compared to the ones of the previous generation, the grandmothers. Data are collected from Swedish parish records, available in the database POPUM at the Demographic Data Base in Umeå. The analysis shows a clear association between infant mortality among mothers and grandmothers. The probability of an infant death for a woman is increased if her mother also had experienced an infant death. Having tested for different approaches of analysis, we found that simple models with few restrictive assumptions gave similar results as more complicated models. Since it is easy to feel confident in the models with the weakest assumptions, we argue that such models are preferred for this type of analysis.